Polymer additives to go? Occurrence of the rubber additive 1,3-diphenylguanidine (DPG) in bottled water - dos Santos, Mauricius Marques (2024)
The occurrence of polymer additives such as 1,3-diphenylguanidine (DPG) has been recently reported in different human samples, including urine and plasma. It has also been widely reported in many sources of drinking water and tap water. Here, we present the first comprehensive assessment of the occurrence of DPG in bottled water samples. A large-volume direct injection LC-MS/MS method was used for the analysis of polymer additives (DPG, DTG, and 6PPD) and six transformation products in different bottled water samples. The use of a 100 μL direct injection LC-MS/MS method enabled detection and quantification limits as low as 0.01 and 0.05 ng/L, respectively, with no interference of potential contaminants from materials commonly used in the laboratory. Out of 63 different samples from 15 different countries, DPG had a detection frequency of 40%, with samples above the limit of quantification having a median concentration of 0.76 ng/L (maximum of 7.4 ng/L). Although the contribution to human exposure from drinking bottled water could explain little of the observed urine concentrations previously reported, the impact from bottled water consumption cannot be neglected and was estimated to be on the same order of magnitude as that of drinking tap water.